Synthesis, Spectral and Antimicrobial Studies of Hg(II), Pd(II) and Pt(II) Complexes with 2-Thiopicoline anilide - Jha, Yogendra; Mishra, L.K. (Asian Journal of Chemistry, 2010)
Complexes of mercury(II), platinum(II) and palladium(II) with the 2-thiopicoline anilide have been prepared and characterized by elemental analysis, magnetic and electronic spectral studies. The square planner geometry to all the palladium(II) and platinum(II) complexes and tetrahedral geometry to the mercury(II) complexes have been suggested. 2-Thiopicoline anilide and its palladium(II) complexes were found to show antimicrobial activity towards the growth of the Subtilis and Micrococcus sp.